Evaluación del reservorio de la formación la luna mediante la caracterización petrofísica de la cuenca de Catatumbo, Colombia (2020)
It is indisputable that the oil industry is the engine of the Colombian economy, however, it has gone through legal, economic, public and even hard work to find oil in recent decades, which is why the detailed characterization of deposits develops static models, established by geological, petrophysical and engineering information, which describes the deposit, the fluids naturally present in the pores of the rocks, the definition of fractures and the distribution of properties in the extension of the area, with the objective of determining the reserves and sets an optimal development plan where the volume of hydrocarbons in the subsoil has already been established, for this reason, it is of vital importance for the exploitation of a deposit, in which, by means of a dynamic model the behavior of fluids in movement through the porous medium is visualized, allowing a plan of exploitation.